Efektywność metod statystycznej analizy wielowymiarowej jako narzędzia segmentacji rynku ubezpieczeniowego - Batóg, Barbara; Mojsiewicz, Magdalena; Wawrzyniak, Katarzyna (The Effectivity of Methods of the Statistical Multidimensional Analysis as Tools of the Insurance Market Segmentation, 2007)
In the paper the authors tried to examine the effectivity of methods of the statistical multidimensional analysis from the point of view of the effectivity of the measurement on the insurances market. The research concerned methodology of the market segmentation on the ground of individual preferences of customers in relation to the products and/or services and of the risk aversion based on utility function. The obtained results were compared with Fred Wagner theory of the insurance market segmentation - with rational and irrational customers. The data used in research were obtained from the questionnaire inquired on 500 households drawn by lot in Poland.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (14); 2007; nr 1169, s. 393-401